Evaluation of oxyfluorfen and quizalofop-ethyl weedicides for weed control in onion (Allium cepa) (Current Horticulture, 2024)
An on-farm trial to evaluate Oxyflurofen and Quizalofop ethyl weedicides for weeds control on Onion (Allium cepa L.) was undertaken during Rabi 2015-16, 2016-17 and 2017-18 at farmer fields in south west district of Najafgarh, New Delhi. The study the herbicidal treatment combination were taken of Oxyfluorfen @ 150 ml/ha + Quizalofop ethyl @ 750 ml/ha foliar spray 35 days after transplanting recorded lower weed density (39.66/m2), dry matter weight of weeds (42.22 g/m2) and higher weed control efficiency (77.61%), followed by treatment1 farmers' practice (Pendimethalin + one hand- weeding) 48.21%. The application of Oxyfluorfen @ 150ml/ha + Quizalofop ethyl @ 750 ml/ha foliar spray 35 days DAT proved to be most effective weed control treatment, recording highest bulb yield (277.44 q/ ha), net return (` 171, 952/ha) and B:C ratio (3.77), followed by farmers' practice (252.22 q/ ha), net return (` 129276/ha) and B:C ratio (3.01). The increased returns as a result of increased quality bulb yield of onion with pre-post herbicides applications showed significant effect with more appreciation.
Keywords: Bulb yield; Farmers fields; Weed management; Weed density